Novel water soluble polymeric sensors for the sensitive and selective recognition of Fe3+/Fe2+ in aqueous media. (5th January 2022) - He, Suyan; Marin, Luminita; Cheng, Xinjian
Graphical abstract: Highlights: Fluorescent water-soluble polymer sensors were obtained by RAFT method. Selective and sensitive recognition of Fe 3+ and Fe 2+ . Fluorophores could be incorporated as RAFT reagent and/or functional monomer. Abstract: Fe 3+ and Fe 2+ are common metal ions in natural water environments and creatures. The development of water-soluble fluorescent sensors for detecting Fe 2+ /Fe 3+ ions was of great significance. In this work, two kinds of boron fluoride dipyrrole (BODIPY) fluorescent small-molecules were synthesized firstly. One of the small molecules contains a thioester bond that can be used as a chain transfer agent to participate in the polymerization process, and the other contains an unsaturated C = C double bond at the meso position. Through the reversible addition-fragmentation chain transfer polymerization (RAFT) polymerization method, methacrylic acid (MAA) and methacrylamide (MAM) were used as the main monomers, and small molecular fluorescent monomers were introduced to the end of the main chain. In this way, fluorescent macromolecules were obtained. The polymers were water soluble owing to the presence of long enough hydrophilic carboxyl and amide chains. These fluorescent probes exhibit high sensitivity to Fe 2+ /Fe 3+, good selectivity, and anti-interference of other ions. The detection limit for Fe 2+ was as low as 2.3 × 10 −7 M, and the detection limit for Fe 3+ can reach up to 4.5 × 10 −7 M. The results show that these probes can be used as good sensors to identify Fe 2+ and Fe 3+ . Moreover, the fluorophores could be incorporated into polymer chains as the RAFT reagents and/or functional monomers.